Isotherm, Thermodynamic, and Kinetics Studies of Iodide Adsorption on The Al_SBA-16 Mesoporous Nanomaterial as Radiopharmaceutical Vehicle Candidate - Maria Christina Prihatiningsih; Sri Sundari Retnoasih; Athanasia Elra Andjioe; Noor Anis Kundari; Edy Giri Rachman Putra (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
In order to investigate the potential of Al_SBA-16 Mesoporous Nanomaterial as a candidate for radiopharmaceutical vehicles, the studies of kinetics, thermodynamic, and in vitro stability of Iodide adsorption onto the nanomaterial have been carried out. The adsorption study was conducted at different temperature, time, and iodide concentration and observed with spectrophotometric techniques. The isotherm adsorption was fitted with Langmuir and Freundlich model and the thermodynamic parameters were determined at temperatures of 293K, 301K, 308K, and 313K. Moreover, the adsorption kinetics was analyzed in terms of pseudo first order model for Al_SBA-16 Mesoporous Nanomaterial and Iodide and pseudo second order in overall reaction. The activation energy was determined by using Arrhenius equation, meanwhile, the in vitro stability testing was conducted in phosphate buffer saline at pH variation for 5.5 to 7.0, and at temperature variation for 20C to 45C and at testing time variation for 6 to 48 hours. The result indicate that the adsorption obeys the Langmuir isotherm model and has a tendency to be chemical adsorption with a value of H was -116.641 kJ/mol and the nature of spontaneous reactions. The adsorption process followed the pseudo-first-order model and the apparent activation energy was 41.26 kJ/mol. In the present research work, the in vitro stability data were evaluated using P-Value and the theory of Hypothesis Testing or Fisher's significance test. The result of hypothesis testing show that, the adsorption of iodide onto Al_SBA-16 Mesoporous Nanomaterial were highly stable under the experimental conditions adopted.